Effects of Superheated Steam on Flavonoids and Antioxidant Activity in Tartary Buckwheat Flour - Mengyuan ZHAO; Xiangyu WANG; Panpan SHANG; Haiqing LÜ; Renyong ZHAO (Shipin gongye ke-ji)
To inhibit the conversion of rutin to quercetin, tartary buckwheat flour was treated with superheated steam and the effects of steam temperature and treatment duration on rutin-degrading enzyme activity, flavonoids, and antioxidant activity were investigated. As treatment temperature increased, phenolic and flavonoid contents first increased and then decreased, phenolic and flavonoid contents were maximal at a steam temperature of 220 ℃, and increased by 37.53% and 14.22%, respectively. Phenolic and flavonoid contents in tartary buckwheat flour fluctuated slightly with changes in treatment duration. When duration of exposure to superheated steam exceeded 6 min, phenolic and flavonoid contents decreased gradually. The change in rutin content was similar to that of flavonoids. When steam temperature was 220 ℃ and treatment duration was 4 min, rutin content was maximal. When steam temperature exceeded 300 ℃ and treatment duration exceeded 6 min, rutin content decreased and quercetin content increased significantly. Rutin-degrading enzyme activity decreased significantly (P<0.05) after exposure to steam. In vitro antioxidant activity (redox ability and DPPH/ABTS+ free radical scavenging ability) of tartary buckwheat powder increased and then decreased. Under certain conditions, superheated steam treatment significantly improved the quality of tartary buckwheat by increasing flavonoid content and antioxidant activity, inactivating rutin-degrading enzymes, inhibiting rutin hydrolysis, and reducing quercetin generation.